OPTIMALISASI INVESTMENT OPPORTUNITY SET (IOS) MELALUI PENINGKATAN PROFITABILITAS - Mahirun; Muhammad Rafli Ahliansyah (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The purpose of this study was to test and analyze the research model on the effect of profitability on the investment opportunity set. Other variables that we suspect influence the investment opportunity set are the capital structure and firm value. The objects in this study are companies included in the LQ45 index on the Indonesia Stock Exchange during the period 2013 – 2021. The analytical tool we use is multiple linear regression to test the effect of the independent variables on the dependent variable. The results of the main test on 298 samples over a period of 10 years resulted in profitability findings with the return on equity (ROE) indicator being able to significantly increase the price earning ratio (PER). While other findings are return on assets (ROA) which is used as an indicator of other profitability variables resulting in a positive and not significant effect on the price earning ratio (PER). The capital structure with the debt to assets ratio (DAR) indicator has a negative and significant effect on the price earning ratio (PER), while the negative and insignificant effect with the debt to equity ratio (DER) indicator. In the end, we also found that the market approach to firm value, namely price to book value (PBV), has a significant positive effect on price earning ratio (PER).